Analysis of Principal Policy and Digital Literacy Introduction Model for Early Childhood - Pusvyta (Universitas Negeri Semarang, 2026)
This study aims to determine the Principal's policy for introducing digital literacy to students at TK Muslimat 17 Mathlabul Huda Lamongan, the challenges and opportunities in implementing the policy, the learning model used to introduce digital literacy. The study was conducted using a qualitative descriptive approach. Data collection was conducted through interviews, documentation, and observation. Data validity was tested by triangulating sources, time, and techniques. The results show that the principal's policy for introducing digital literacy is optimizing curriculum implementation. The challenges include limited infrastructure, the lack of education and training for introducing digital literacy in schools, not all parents are digitally literate, and parents' difficulties in guiding their children. Meanwhile, the opportunities include parents' willingness to participate in parenting and reflection activities, and support from internal and external stakeholders. The introduction of digital literacy is carried out using the STEAM (Science, Technology, Engineering, Art, Mathematics) instructional model and collaborative learning model. The advantages of the STEAM model are that it can encourage critical thinking, creativity, collaboration and togetherness, helping to understand the relationship between concepts and the real world. The disadvantages are: it requires thorough technical and practical preparation, and takes a lot of time. The advantages of the collaborative learning model are: making it easier for teachers to introduce digital literacy with limited equipment, increasing responsibility, togetherness, social skills, motivation, courage and self-confidence. Meanwhile, the disadvantages are: it requires long time for preparation, supervision, guiding and learning, and can cause conflicts due to fighting over learning media.